THE ROLE OF THE TEACHER IN SOCIETY. EDUCATION AND UPBRINGING (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article examines the role of teachers in society, with a particular focus on education and training. Teachers play a crucial role in shaping the minds, character, and future of individuals. They facilitate learning, provide guidance and support, and contribute to the overall development of students. The article highlights the various responsibilities and contributions of teachers, including curriculum design, instructional delivery, assessment, mentorship, and fostering a positive learning environment. Additionally, it explores the importance of teachers' ongoing professional development and their role in promoting educational equity and access. The article concludes by emphasizing the significant impact teachers have on individuals, communities, and society as a whole.